Meningkatkan Hasil Belajar Siswa Melalui Penerapan Pembelajaran (Problem Based Learning) Pada Mata Pelajaran Matematika di Kelas V SD Negeri 241 Palembang - Desi Marlina Sari; Effendi Effendi; David Saputra (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to improve the learning outcomes of class V students at SD Negeri 241 Palembang in the Mathematics Education subject using a middle Problem Based Learning. The methodology applied is Classroom Action Research (PTK) with two stages. The research participants consisted of 27 fifth grade students at SD Negeri 241 Palembang. Research findings show a significant increase in student learning outcomes. In the initial stage, the average student score reached 67.4 with classical completeness of 65.8%. In stage I, the average score increased to 75,9 with classical completeness of 75.3%. Stage II showed further progress with a mean score of 84,4 and classical completion of 88.1%. This research concludes that the middle Problem Based Learning approach is effective in increasing student learning outcomes in Mathematics Education lessons.